Vulnerability factors of snake bite patients in China - Wenjie Hao; Chuanzhu Lv; Xingyue Song; Lanfen He; Juntao Wang; Yanlan Hu; Yu Chen; Yong Gan; Shijiao Yan; Xiaotong Han (BMC, 2024)
Abstract Objective To analyze the vulnerability factors of snakebite patients in China. Methods Multi-stage random sampling was used as the main sampling method and snowball sampling as the auxiliary sampling method. The knowledge, attitude and behavior of snakebite among Chinese residents were investigated. Non-parametric test was used to compare the percentage differences in residents' knowledge, attitude and behavior of snakebite, and generalized linear regression analysis was used to analyze the influencing factors, and the vulnerability factors of snakebite patients were comprehensively analyzed. Results A total of 6338 subjects were included in this study, of which 68.4% were males, and 58.6% were farmers, workers and service personnel. The median total score of knowledge, attitude, and behavior was 26 (22,36). The patients who were improperly treated after injury were ligation proximal to the affected area (23.43%), squeezing (21.82%), and oral and suction wounds (8.74%). Did not go to hospital due to poverty (1351 cases) and did not receive antivenom (2068 cases). There were 21.32% and 32.63%, respectively. Among 4270 patients injected with antivenom 30.7% were vaccinated within 2 h. Among the patients who went to the hospital for treatment (4987), 75.0% arrived at the hospital within 6 h; Among the 4,761 patients who made emergency calls, 37.4% were treated within 0.5 h. Conclusions Snakebite patients in China have weak knowledge about snakebite, low awareness of medical treatment, lack of correct prevention and emergency treatment measures, dependence on folk remedies, poor housing and so on. In addition, there are low availability of antivenoms and unreasonable distribution of medical resources in some areas of China. Multisectoral and multidisciplinary cooperation should be developed to prevent and control snakebites in order to reduce the burden caused by snakebites.